Perlindungan hukum terhadap anak hasil inses perspektif hukum nasional dan maqashid syari’ah - mabruroh, masulatul (Maliki Interdisciplinary Journal, 2026)
Children born from incestuous relationships represent a highly vulnerable group, often facing discrimination, social stigma, and uncertain legal status. In the context of national law, protection for children born from incest establishes a legal bond with the mother, without granting recognition of a relationship with the biological father. This affects their legal identity, protection, and welfare. From the perspective of maqashid syari‘ah, child protection is part of the main objectives of Sharia, namely safeguarding the five fundamental aspects of life: religion, life, intellect, lineage, and property. These principles require the state to guarantee children’s rights to education, healthcare, legal identity, and economic security without discrimination based on birth origin. Although legal instruments such as Constitutional Court Decision No. 46/PUU-VIII/2010 and MUI Fatwa No. 11/2012 provide limited recognition, specific legal protections for children of incestuous origin are still urgently needed. This study recommends strengthening regulation and public education to eliminate discrimination, so justice and child welfare may be upheld in accordance with humanitarian values and Islamic legal principles.